PROSES PERSIAPAN DAN PELAKSANAAN EVENT INDONESIA & TAIWAN ONLINE BUSINESS DAY OLEH PT. MAXIMAINDO - Erika Agnes Saharani; Tuty Herawati (Program Studi MICE, Jurusan Administrasi Niaga, Politeknik Negeri Jakarta, 2023)
The Covid-19 Pandemic that hit Indonesia at the end of 2020 caused economic paralysis. One of the affected industries is the MICE Tourism industry, MICE stakehoders are starting to look for ways to survive. One way to survive is to do activities online or virtually. Therefore, PT. Maximaindo also began to switch from event contractors to organizing virtual events by holding Indonesia & Taiwan Online Business Day regarding manufacturing machines and plastics which was held on December 7-9, 2021. This research was conducted to find out the preparation and implementation process of the Online Business Matching held between Taiwan and Indonesia, and also to find out the obstacles that existed during the event. In this study, the authors used qualitative methods with data collection through observation, interviews, library methods, and documentation. The findings obtained are in the preparation process, it is necessary to collect a filtered database and make a registration form, then contact prospective buyers and suppliers. The last stage is to compile a meeting schedule and ask for confirmation from both parties. For implementation, what needs to be prepared is a laptop, wifi, and Zoom background. The event opened with remarks and then buyers and suppliers will enter the waiting room and the operator will move buyers and suppliers according to the schedule and predetermined room. There are obstacles during preparation and implementation, one of which is network or device constraints, and problem when contacting buyers.